Covidogram as a simple tool for predicting severe course of COVID-19: population-based study - Jarkovsky, Jiri; Benesova, Klara; Cerny, Vladimir; Razova, Jarmila; Kala, Petr; Dolina, Jiri; Majek, Ondrej; Sebestova, Silvie; Bezdekova, Monika; Melicharova, Hana; Snajdrova, Lenka; Dusek, Ladislav; et al. (BMJ open, 2021)
OBJECTIVES: COVID-19 might either be entirely asymptomatic or manifest itself with a large variability of disease severity. It is beneficial to identify early patients with a high risk of severe course. The aim of the analysis was to develop a prognostic model for the prediction of the severe course of acute respiratory infection. DESIGN: A population-based study. SETTING: Czech Republic. PARTICIPANTS: The first 7455 consecutive patients with COVID-19 who were identified by reverse transcription-PCR testing from 1 March 2020 to 17 May 2020. PRIMARY OUTCOME: Severe course of COVID-19. RESULT: Of a total 6.2% of patients developed a severe course of COVID-19. Age, male sex, chronic kidney disease, chronic obstructive pulmonary disease, recent history of cancer, chronic heart failure, acid-related disorders treated with proton-pump inhibitors and diabetes mellitus were found to be independent negative prognostic factors (Area under the ROC Curve (AUC) was 0.893). The results were visualised by risk heat maps, and we called this diagram a 'covidogram'. Acid-related disorders treated with proton-pump inhibitors might represent a negative prognostic factor. CONCLUSION: We developed a very simple prediction model called 'covidogram', which is based on elementary independent variables (age, male sex and the presence of several chronic diseases) and represents a tool that makes it possible to identify-with a high reliability-patients who are at risk of a severe course of COVID-19. Obtained results open clinically relevant question about the role of acid-related disorders treated by proton-pump inhibitors as predictor for severe course of COVID-19.
Keywords: Research; gastroduodenal disease; Humans; lidé středního věku; Female; výzkum; Aged; dospělí; organisation of health services; senioři; lidé; reprodukovatelnost výsledků; Adult; COVID-19; ženské pohlaví; Male; Reproducibility of Results; Middle Aged; Czech Republic; Aged, 80 and over; senioři nad 80 let; Česká republika; mužské pohlaví; SARS-CoV-2